2015
DOI: 10.54207/bsmps1000-2015-t36w5g
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Alien Species of Vindhyam Range of Uttar Pradesh, India their Source of Origin and Use Potential

Abstract: Vindhyam range of Uttar Pradesh, India comprises 149 alien species under 106 genera belonging to 44 families. On analysing the data it was observed that 73% of alien species are from tropical America including South America and 10.5% from tropical Africa. Present study is based on several years of intensive exploration of the area. Excursions were under taken in different areas at regular intervals. During excursions information regarding important alien species with their legitimate botanical name, families, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…The predominance of annuals (67%) in our oristic list indicates the disturbing site's soils as reported by several researchers (Foster and Stubbdeck 1980;Tilman 1983). Singh et al (2010) also reported the dominance of annuals in the total invasive alien ora of UP. The high fraction of annuals may be due to a variety of agricultural and other anthropogenic activities (Rejmanek and Richardson 1996;Weber et al 2008) and are more plastic and capable of invading a larger geographical area compared to perennials (Huang et al 2010;McDougall et al 2011).…”
Section: Discussionsupporting
confidence: 74%
“…The predominance of annuals (67%) in our oristic list indicates the disturbing site's soils as reported by several researchers (Foster and Stubbdeck 1980;Tilman 1983). Singh et al (2010) also reported the dominance of annuals in the total invasive alien ora of UP. The high fraction of annuals may be due to a variety of agricultural and other anthropogenic activities (Rejmanek and Richardson 1996;Weber et al 2008) and are more plastic and capable of invading a larger geographical area compared to perennials (Huang et al 2010;McDougall et al 2011).…”
Section: Discussionsupporting
confidence: 74%
“…Being a holy city and prominent tourist place, Varanasi is visited by a large number of tourists and this may be one of the major causes of spread of IAPs in the district (Singh, Singh, & Singh, 2013). Singh et al (2013) recorded 120 species of IAPs from different habitats of Varanasi including riparian zones. These species affect native biodiversity and human well‐being in the riparian habitats of the Ganga River (Singh et al, 2013; Singh & Singh, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Singh et al (2013) recorded 120 species of IAPs from different habitats of Varanasi including riparian zones. These species affect native biodiversity and human well‐being in the riparian habitats of the Ganga River (Singh et al, 2013; Singh & Singh, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This high reproductive potential is achieved by partitioning of reproductive capital into a large number of propagules that are minute, light, and wind dispersed. 38 Various other workers have also reported the dominance of Asteraceae among invasive alien species in India 39,40 and in Indian Himalayan region. 41 Family Asteraceae is followed by Fabaceae one among the largest families of alien flora of India and having the potential of nitrogen fixing capacity would be helpful to them in colonizing the empty niches.…”
Section: Discussionmentioning
confidence: 95%